Exploring perceived dignity among AIDS/HIV patients in behavioral disease counseling centers in Iran - Ali Vafaee Najar; Sima Zofnoun; Jamshid Jamali; Fatemeh Kokabi; Elaheh Hooshmand (Shahrekord University of Medical Sciences, 2023)
Background and aims: People with HIV/AIDS may encounter several problems, such as discrimination and social challenges, which affect their perceived dignity. The purpose of this study was to evaluate the perception of dignity among HIV/AIDS patients in a healthcare setting in Iran. Methods: This cross-sectional study was done on HIV/AIDS patients referring to behavioral disease consulting centers affiliated with a mainstay of health and medical education, Iran, in 2023. The study sample consisted of 220 patients selected using the available sampling method. A patient dignity questionnaire was used to collect data. The validity and reliability of the questionnaire were confirmed. The collected data were analyzed by SPSS 25 software using parametric tests. Results: Findings showed that the mean age of patients was 37; 51.1% of participants were men, 46.1% were married, 4.2% had primary education, 55.9% were employed, and 66.7% were in the asymptomatic stage of the disease. The overall score for perceived dignity was 1/96 out of 5 and was evaluated well. The mean scores for mental abilities and perceptions, personal and social concerns were 1.37 (SD: 0.44), 2.85 (SD: 0.94), and 1.37 (SD: 0.48), respectively. There was also a statistically significant relationship between perceived dignity score and the levels of education and being under treatment. Conclusion: Although the studied patients had a well-perceived status of dignity and were satisfied with their abilities and social communication, their greatest concern was personal concerns. It is recommended that psychological support and therapies be provided to these patients.